Genetics of COPD - Hall, Ian (Henry Stewart Talks, 2014)
COPD-important world-wide cause of morbidity and mortality, Clear evidence of a genetic contribution to disease risk, Genome wide association studies have identified genes predicting lung function, Role of these genes in COPD pathophysiology
Archived at 2023/07/31